GOVERNANCE CHALLENGES AND OPPORTUNITIES: THE ROLE OF THE MUKIM INSTITUTION IN CUSTOMARY FOREST MANAGEMENT IN ACEH PROVINCE, INDONESIA - Nurhaliza Nurhaliza; Teuku Muttaqin Mansur; M Adli Abdullah; Efendi Efendi; Muazzin Muazzin; Andika Priandana Sunoko (Universitas Syiah Kuala, 2025)
The role of the Mukim institution, as a unique customary body under the Aceh special autonomy system, in managing customary forests has been a subject of debate. The limitations and challenges faced by Mukim in fulfilling its responsibilities, particularly in light of contemporary environmental and legal pressures, remain unclear. This study employs a doctrinal-empirical investigation, utilizing a literature review and interviews with respondents and informants. The empirical research was conducted in Mukim Lampanah, Seulimeum District, and Mukim Blang Mee, Lhoong District, both situated in Aceh Besar Regency. The findings indicate that the Mukim holds a position of authority in the governance of customary forests, playing a crucial role in the management and oversight of natural resources within their designated territories. They possess the authority to designate customary forests. However, their capacity to meet these responsibilities is hampered by a lack of personnel within the Mukim institution and limited engagement from local administrations, particularly in terms of policy support and collaborative forest management efforts. Additionally, their efforts often conflict with national forestry management policies. To enhance the effectiveness and sustainability of forest management, it is essential to establish stronger collaboration and coordination mechanisms between the Mukim and government forestry agencies. This would facilitate better alignment of policies and improve overall forest governance.